Methadone Maintenance Therapy (MMT) and Alternatives in Opioid Use Disorder: Reviewing the latest advancements, outcomes, and challenges in substitutional therapy for opioid addiction - literature review - Koszyczarek, Karolina; Kotowska, Maja; Zamirska, Wiktoria; Ziemiański, Albin; Zięba, Katarzyna; Zygmunt, Anna; Smuszkiewicz-Różański, Paweł; Różańska-Smuszkiewicz, Gabriela (Journal of Education, Health and Sport, 2024)
Introduction and Purpose: Opioid addiction is a serious challenge for public health worldwide, and methadone maintenance therapy (MMT) is a key therapeutic approach. This review intends to provide an up-to-date summary of the pathophysiology, clinical manifestation, diagnostic techniques, and treatment options for Opioid Use Disorder. Materials and methods: The literature available in PubMed, Scopus, and Google Scholar databases was reviewed using the following keywords: "MMT," "methadone maintenance therapy", “maintenance therapy”, "opioid use disorder", "opioid addiction," "methadone”, ”naloxone” “naltrexone”, and “buprenorphine”. State of Knowledge: This review examines current approaches in maintenance therapy for Opioid Use Disorder (OUD). In the study, we focus on treatments using methadone, buprenorphine, naloxone, and naltrexone. It focuses on recent advancements, comparing the effectiveness, safety, and patient outcomes of these therapies. Key challenges in treatment accessibility and implementation are also discussed, providing an updated overview of the field and identifying areas for future research in opioid addiction therapy. Conclusion: There is a series of studies researching the psychological and behavioral problems associated with opioid addiction. This research has given medical practitioners valuable guidance on effective management techniques. According to the authors, compared to other alternative treatment methods, methadone maintenance therapy (MMT) is still considered the most effective pharmacotherapeutic method in the treatment of opioid addiction. Nevertheless, ongoing research is essential to improve diagnostic processes, develop innovative therapies, and enhance the overall quality of care for those affected by these challenges.